Pelestarian Kesenian Ronggeng Nagari Simpang Tonang Kecamatan Dua Koto Kabupaten Pasaman - Aulia Putra; Syeilendra Syeilendra (FBS Universitas Negeri Padang, 2020)
This writing aims to reveal about preservation as the cultural heritage of the Nagari Simpang Tonang community. The research in this thesis uses a qualitative method approach, in the form of qualitative descriptive. The results of the study are describing cultural phenomena regarding the preservation of Ronggeng Nagari Simpang Tonang arts. Data collection is done by direct observation techniques, with the approach of observation, interviews, recording and recording and using documentation and literature study. The preservation of Ronggeng's art now depends on the willingness, effort and efforts of local artists. It means that the life and death of Ronggeng art lies in the hands of artists. Local artists are the only people who are responsible and responsible today for the preservation of Ronggeng art. Whereas the public only wants to be a loyal audience. If the number of artists decreases and at one time all of them are no longer physically able to activate or they have died, it can be predicted Ronggeng art will be extinct in Nagari Simpang Tonang. Therefore, Ronggeng's art today is very dependent on the efforts and efforts of artists in their activitiesboth formally and informally.